Early onset breast cancer: differences in risk factors, tumor phenotype, and genotype between North African and South European women - (:unkn) unknown (My University, 2017)
PURPOSE: This report compares the risk factors, the tumor phenotypes, and the BRCA1/BRCA2 genotype of early onset breast cancer (EOBC) patients between Southern Europe and North Africa. METHODS: Four hundred and fifty six women with invasive EOBC (<=40~years) were prospectively included from four centers in France (n~=~270) and four centers in North Africa (Algeria, Egypt, Morocco, Tunisia; n~=~186). Life style, tumor phenotype, familial history, BRCA1/BRCA2 genotype were compared between the two populations. RESULTS: We found an older age at menarche, a higher number of childbearing, a more frequent breastfeeding, a higher body mass index, a lower use of oral contraceptives in North African women compared to French women. TNM stage at diagnosis was higher in North African women than in French women. North African women had a lower incidence of triple negative and proliferative (Ki 67 index~\textgreater~20%) tumors. There was a lower rate of BRCA1 mutation in North Africa (7 vs. 15%, P~=~0.02). Three putative BRCA1/2 founder mutations were identified in North Africa. CONCLUSIONS: In EOBC, we found~significant differences in risk factors, phenotype and a higher incidence of BRCA1 mutations in Southern Europe as compared to North Africa. The worst prognosis previously reported for EOBC in North Africa is more likely due to a higher stage at diagnosis than to a more aggressive phenotype, since triple negative tumors are more common in Southern Europe and advanced tumors in North Africa.
Keywords: African Research